A New Form of Soft Functions in Soft Topological Spaces - P. Anbarasi Rodrigo, S. Anitha Ruth (Mathematical Statistician and Engineering Applications, 2020)
In this paper, we introduce a new category of soft function called Š - continuous function. Also we study in detail the properties of Š - continuous function, Š irresolute function and its relation with other Š function. All these findings will provide a base to researchers who want to work in the field of soft topology and will help to establish a general frame work for applications in practical fields.